Analisis Pengaruh Belanja Daerah, DBH dan DAU terhadap Pendapatan Asli Daerah di Provinsi Jawa Tengah - Helda Rafsanjani; Suharno Suharno (Universitas Batanghari Jambi, 2022)
Regional autonomy is a policy in which the government system shifts from a centralized system to a decentralized one. The increase in the Balancing Fund is expected to be followed by an increase in regional fiscal independence in the form of a significant increase in Local Revenue (PAD) as a reflection of regional independence. The purpose of this study was to determine the effect of Regional Expenditure, Revenue Sharing Funds (DBH), General Allocation Funds (DAU) on Regional Original Revenues in Central Java Province. This research uses a quantitative approach with a regression test. The results showed that the allocation of Regional Expenditures and Revenue Sharing Funds have a positive effect on Regional Original Revenues, while the General Allocation Funds have a negative effect on Regional Original Revenues.